2018
DOI: 10.1177/1035719x18795539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluators and the enhanced Commonwealth performance framework

Abstract: The enhanced Commonwealth performance framework was introduced on 1 July 2015 under the Public Governance, Performance and Accountability Act 2013. It should allow the Australian Parliament and public to understand the proper use of public resources, whether the accountable authorities of Commonwealth entities and companies are achieving their purposes and who is benefitting from Commonwealth activity. Demonstrating the achievement of purposes amounts to demonstrating outcomes and impacts. It requires Commonwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…LaVelle, et al (2022) most recent focus on imposter syndrome in evaluators provides strong stimulus for further work in the Australian context. Morton & Cook (2018) flag the potential for the expansive evaluation toolkit (and evaluators’ expertise) to ‘build capability of “performance professionals” across the public sector’ (p. 141).…”
Section: Discussionmentioning
confidence: 99%
“…LaVelle, et al (2022) most recent focus on imposter syndrome in evaluators provides strong stimulus for further work in the Australian context. Morton & Cook (2018) flag the potential for the expansive evaluation toolkit (and evaluators’ expertise) to ‘build capability of “performance professionals” across the public sector’ (p. 141).…”
Section: Discussionmentioning
confidence: 99%
“…The United Kingdom’s What Works Network works with national and local government officials to support their efforts to craft evidence-based approaches to solving problems (What Works Network, 2018). The Commonwealth of Australia has similarly taken steps to embed evaluation within government practice through the Australian Public Governance, Performance and Accountability Act (Barrett, 2018; Morton & Cook, 2018).…”
Section: The Rise Of Evidence-based Policymakingmentioning
confidence: 99%
“…Limited compliance has been found in three agencies (ANAO, 2017) and a Review of implementing the Act found the 'quality of performance reporting needs to improve' (Alexander & Thodey, 2018, p. 3). DoF has recognised programme evaluation contributes to this performance (Morton & Cook, 2018). Measuring performance is linked with achievement by DoF's Resource Management Guide (RMG) 131: 'Performance measures should enable an entity to demonstrate its performance in achieving its purposes or key activities over time' (DoF, 2020, p. 11).…”
Section: Implementing the Pgpa Actmentioning
confidence: 99%